IDENTIFIKASI PERMASALAHAN DAN REKOMENDASI SOLUSI SUMUR GAS X YANG MATI SECARA KOMPREHENSIF DENGAN MENGGUNAKAN ANALISA KEMAMPUAN ALIR RESERVOIR, TRANSIEN TEKANAN DAN SIMULASI RESERVOIR - Pramana, Edho
Problem in gas well can be identified using test data analysis and the IPR curve of the formation. This study is about the problem in shutted well for several years and then it is opened early (in 2011). The comparison of IPR when the well was tested for the first time and then shutted for 4 years with the IPR in 2011 (when the well opened) was much different. This study is to analyze the problem using three different approaching methods, the first is from Drill Stem Test Data analysis (using pressure transient analysis), comparison of IPR in 2007 and 2011, and the last is using simulation of the reservoir to analyze the problem and to do the prediction of production performance. From those approaching methods we can take conclusions to help making decisions for the next step to treatment this well. The result from this study shows that the problem in gas well X in Y field is not caused by reservoir damage. It is strongly indicate that the problem caused by broken tools used in the gas well X. This analysis can prove the first hypothesis is right. Beside that, using reservoir simulator, we can find the production performance of well X, for the rate is 2 MMSCFD this well can give plateu time for 5 years and if it produced in 14 MMSCFD or 19 MMSCFD, it can give plateu time three or one month.